Correlation of Interpersonal Relationship and Work Stress among Female Health Care Staff of a Private Hospital in Denpasar Bali - Manoharan, Thunissha; Purnawati, Susy; Krisna Dinata, I Made (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 7 No 1 (2021): Volume 7 N0 1 June 2021DO - 10.24843/JEI.2021.v07.i01.p09, 2021)
Interpersonal relationship and work stress are important elements in occupational health. To study the correlation of interpersonal relationship and work stress among female health care staff. This research is a cross sectional analytical study carried out in Surya Husadha Hospital Denpasar among female health care staff from 5 strata of professions; ICU doctors, nurses, pharmacists, medical lab technicians and administrative staff. About 82 samples are involved in this study which are drawn by multistage random sampling. Majority staff (28%) are known to be experiencing moderate interpersonal relationship with moderate level of work stress. The value of correlation coefficient of Pearson between interpersonal relationship and work stress is r = -0.572 and p = 0.001. The p value indicates a significant correlation between interpersonal relationship and work stress whereas the value of r = -0.572 indicates a negative relationship with a moderate strength of correlation between the two variables whereby stronger the interpersonal relationship, lower the stress level or vice versa. Hence, the hypothesis of this research is accepted. There is a moderate negative correlation between interpersonal relationship and work stress among female health care staff in Surya Husadha Hospital Denpasar. The negative correlation means if interpersonal relationship decreases then work stress increases or vice versa. This study can benefit the future researchers to determine ways in enhancing the interpersonal relationship in order to decrease the level of stress among female health care staff also in improvising health care provider to the society